Synthesis and biological evaluation of salpichrolide analogues as antiestrogenic agents - Sonego, Juan Manuel (2014)
The antiestrogenic activity of three natural salpichrolides A, G and B (1, 3 and 4) and of five synthetic analogs containing an aromatic D ring and a simplified side chain (5–9), was evaluated on MCF-7 cells. The 2,3-ene-1-keto steroids 8 and 9 were obtained from 3β-acetoxy-17(13→18)-abeo-5αH-pregna-13,15,17-trien-20-one, the key step for these syntheses being a Wharton carbonyl rearrangement of a 1,2-epoxy-3-keto steroid to the allylic alcohol using hydrazine hydrate. The antiestrogenic activity was evaluated by performing dose–response experiments in ER(+) MCF-7 breast cancer cells. Dose-dependent proliferation was quantified via [3H]-thymidine incorporation after 3 days treatment. Salpichrolides A, G and B and analogs 5, 8 and 9 were active as antiestrogens with compound 9 being the most active of the synthetic analogs. Compounds 5 and 9 were also evaluated against the ER(−) cell line MDA-MB-231 and shown to be inactive.